Customer Relationship Management Website Application in Monitoring Marketing and Sales Activities at Educourse.id Surakarta Branch: Penerapan Website Customer Relationship Management Untuk Memantau Aktivitas Marketing dan Penjualan Pada Educourse.id Cabang Surakarta - Sherly Anindhya Meyra Love Tiananta; Supriyono (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
Customer Relationship Management (CRM) supports a company to provide real-time customer service and build relationships with each customer through the use of customer information. This CRM method emphasizes the human element. This activity is intended to monitor the effectiveness of the implementation of the CRM method. Measurements are carried out through data collection obtained from direct observation of consumers and the Educourse.id marketing team. The results found are that the company's CRM management can monitor marketing activities in carrying out visits to consumers and showing activities in each branch of the company. The implementation of CRM can increase sales by monitoring marketing activities through qualified leads. Monitoring activities begins when consumers are visited by the marketing team until the follow-up at the MoU (Memorandum of Understanding) stage. In addition, the performance of each branch can also be seen to increase or decrease. Thus, the company can predict long-term sales, marketing activities, and potential cooperation with each consumer. Cooperation in the form of coding and robotics learning.